Perhutanan Sosial dan Peubah-peubah Sosiologi yang Harus Diperhatikan: Sebuah Tinjauan Teoritis - Hendarto, Kresno Agus (Jurnal Manajemen Hutan Tropika, 2003)
The inability of industrial forestry to benefit the rural poor or address the increasing rate of deforestation in Indonesia has led to a major shift in direction of forest resource management. In national forestry meeting, July 10 until 12, 2002, Minister of Forestry declared social forestry as national forestry program. Social science as a whole has had very minor role in forest management over the last century. Economics was the sole social science discipline welcomed by forest managers in the old paradigm of forest management. Economists helped forest managers determine the optimal combination of inputs to maximize financial benefits from a given parcel of forestland. They also assisted with market analysis, labor studies, and other financial dimensions of forest management. In this paper, we will first review the conceptual of social forestry. We also review literature on sociological variables that can help policy-markers improve the quality of public involvement in social forestry planning and development. Finally, we will give alternative additional of sociological variable social forestry in Indonesia such as gender equality, fairness, appreciation for local spesies, and mutual trust in stakeholder that must be taken note.